Joost van den Vondel (1587-1679) Dutch Playwright in the Golden Age - Bloemendal, Jan (Drama and Theatre in Early Modern Europe, 2012)
Joost van den Vondel (1587-1679) was the most prolific poet and playwright of his age. During his long life, roughly coincinding with the Dutch Golden Age, he wrote over thirty tragedies. He was a famous figure in political and artistic circles of Amsterdam, a contemporary and acquaintance of Grotius and Rembrandt, but in general well acquainted with Latin humanists, Dutch scholars, authors and Amsterdam burgomasters. He fuelled literary, religious and political debates. His tragedy 'Gysbreght van Aemstel', which was played on the occasion of the opening of the stone city theatre in 1638, was to become the most famous play in Dutch history, and can probably boast holding the record for the longest tradition of annual performance in Europe. In general, Vondel's texts are literary works in the full sense of the word, complex and inexhasutive; attracting attention throughout the centuries. Contributors include: Eddy Grootes, Riet Schenkeveld-van der Dussen, Mieke B. Smits-Veldt, Marijke Spies, Judith Pollmann, Bettina Noak, Louis Peter Grijp, Guillaume van Gemert, Jürgen Pieters, Nina Geerdink, Madeleine Kasten, Marco Prandoni, Peter Eversmann, Mieke Bal, Maaike Bleeker, Bennett Carpenter, James A. Parente, Jr., Stefan van der Lecq, Jan Frans van Dijkhuizen, Helmer Helmers, Kristine Steenbergh, Yasco Horsman, Jeanne Gaakeer and Wiep van Bunge